Factors affecting savings among Small Scale Cacao Farmers in Rural households the case of Barangay Subasta, Calinan district, Davao City - Gica, Eugenio Junior A. (2016)
This study was conducted in Barangay Subasta, Calinan, Davao City. First-hand interview among the small scale cacao farmers in the area through generated survey forms were used in collecting primary data and achieved 92.5% response rate and approximately 93% of the small scale farmers in barangay Subasta have set aside certain amount of their income of savings purposes. Using the Likert Scale, trust in identifying which institution to choose to open savings is the most preferred attribute on why farmers choose to save among financial institutions. Furthermore, farmers are motivated to save because of their emergency needs rather than investment. Data was analyzed with the aid of descriptive statistics and regression model. Among the determinants, family labor size, farm size, annual household income, access to cooperatives and access to microfinance institutions were identified to be significant. Most of the cacao farmers lack knowledge in terms of understanding the importance of saving. Encouraging the financial institutions to implement personal service provision will enhance the savings and investment functions in the area. Cooperatives in Barangay Subasta, Calinan, specifically Subasta Intergrated Farmers Inc. should provide financial services such as savings and loans. The government through relevant ministries needs to come up with programs that promote the livelihood of farmers and incentives such as improved technology, appropriate farm support services.